Trampoline gymnastics: the Brazilian participation at international championships - the Olympic games still a dream - Bortoleto, M.; Carrara, P.; Guarniei Roveri, M. (Science of Gymnastics Journal, 2018)
Since the modern trampoline was built by George Nissen and Larry Griswold around, 1934 in USA, this equipment and its use has suffered drastic changes. Its development was decisive in order to Trampoline Gymnastics to be included at the Olympic Games program in 2000. In Brazil its practice started in the 1980`s, and has been only integrated the Brazilian Gymnastics Federation in 1999. The purpose of the study is to analyze the Brazilian participation in the international trampoline gymnastics championships. Data collection was performed by the documental and bibliographic research of main international trampoline gymnastics competitions. The results show that, even though Brazil is the leader in South America with relevant participation in the continental level, the first participation at an Olympic Games had only been possible in 2016, because Brazil was the host country. We conclude that the Brazilian participation in World Championships and in the Olympic Games is not relevant. Finally, the lack of adequate equipment, the bad condition of the training centers, the absence of regular and official coaching education programs and the lack of support for the clubs, shows that this gymnastics discipline is not a current priority for the National Sports authorities, hindering its development internally.